Prevalence of Coronavirus Disease-2019 Among Anaesthesiologists and Anaesthesia Technicians in Al Anbar Governorate, Iraq - Yahya Mohammed; Mohammed Mohammed; Khalida Rajab (Al-Anbar Medical Journal, 2023)
Background: Anesthesiologists and their assistants, who have extensive skills and powerful impact, are major contributors to the COVID-19 management team. However, the procedures they perform expose them to the danger of infection.Objectives: To estimate the prevalence rate of COVID-19 among anesthesiologists and the assistant staff in Al Anbar Governorate and factors that might affect the rate of infection.Materials and Methods: A prospective survey study was conducted for the anesthesiologists and anesthetist assistants who worked in any hospital (12 in number) in Al Anbar Governorate, Iraq. The agreed participants were contacted by phone. Demographic and clinical data were recorded for each participant.Results: Of 214, there were 100 participants responded to the questionnaires with a response rate of 46.7%. The prevalence of COVID-19 among them was 93%. The majority of the subjects were from the age group ≤ 40 years (65%), males (67%), and non-smokers (73%).  Most of the individuals were sub-staff (90%), with a service duration of 1-2 years (44%), work in the operative room (60%), and they were not worked in an isolation hall (58%). There was no statistically significant difference between infected and non-infected groups regarding the above-mentioned variables (P-value > 0.05). The majority of the participants (92%) were vaccinated. There were 4 out of 92 from the vaccinated group and 3  out of 8 from the non-vaccinated group got an infection with a statistically significant difference (P-value = 0.0001). The majority (83) of the participants were taken the Pfizer vaccine. Most of the infected subjects with mild severity. Besides, there was a statistically significant difference between COVID-19 severity and the timing of the infection (P-value = 0.0001).Conclusion: The prevalence of COVID-19 among the participants was 93%. Vaccination could have a protective effect against the disease.